Characterization of recombinantly expressed matrilin VWA domains - Becker, Ann-Kathrin A. (Protein Expr Purif, 2015)
VWA domains are the predominant independent folding units within matrilins and mediate protein–protein interactions. Mutations in the matrilin-3 VWA domain cause various skeletal diseases. The analysis of the pathological mechanisms is hampered by the lack of detailed structural information on matrilin VWA domains. Attempts to resolve their structures were hindered by low solubility and a tendency to aggregation. We therefore took a comprehensive approach to improve the recombinant expression of functional matrilin VWA domains to enable X-ray crystallography and nuclear magnetic resonance (NMR) studies. The focus was on expression in Escherichia coli, as this allows incorporation of isotope-labeled amino acids, and on finding conditions that enhance solubility. Indeed, circular dichroism (CD) and NMR measurements indicated a proper folding of the bacterially expressed domains and, interestingly, expression of zebrafish matrilin VWA domains and addition of N-ethylmaleimide yielded the most stable proteins. However, such proteins did still not crystallize and allowed only partial peak assignment in NMR. Moreover, bacterially expressed matrilin VWA domains differ in their solubility and functional properties from the same domains expressed in eukaryotic cells. Structural studies of matrilin VWA domains will depend on the use of eukaryotic expression systems.